2010
DOI: 10.1002/sia.3256
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of bacteria and yeast using surface‐enhanced Raman scattering

Abstract: Surface-enhanced Raman scattering (SERS) is a powerful technique used for obtaining chemical information about the moleculesand molecular structures in the vicinity of surfaces of noble metal nanostructures. The chemical information acquired through SERS can be used for not only characterization but also detection and identification. In a clinical setting, rapid and accurate identification of micro-organisms is critical. The biochemical information collected through the SERS spectra can be used for quick ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…A pesar de que existen numerosos reportes sobre la determinación de bacterias utilizando la técnica SERS mediante el uso de nanopartículas de metales nobles en solución [14], en la literatura revisada no encontramos publicaciones que reporten el uso de plataformas nanoestructuradas sólidas de plata para detección de E. coli. La determinación de bacterias patógenas es de vital importancia para la salud pública, debido a que cada día es necesaria la búsqueda de nuevos sistemas de detección con diagnósticos oportunos que permitan obtener una respuesta rápida y confiable de un analito en particular.…”
Section: Resultados 1 Espectro Sers Del áCido Fólicounclassified
See 1 more Smart Citation
“…A pesar de que existen numerosos reportes sobre la determinación de bacterias utilizando la técnica SERS mediante el uso de nanopartículas de metales nobles en solución [14], en la literatura revisada no encontramos publicaciones que reporten el uso de plataformas nanoestructuradas sólidas de plata para detección de E. coli. La determinación de bacterias patógenas es de vital importancia para la salud pública, debido a que cada día es necesaria la búsqueda de nuevos sistemas de detección con diagnósticos oportunos que permitan obtener una respuesta rápida y confiable de un analito en particular.…”
Section: Resultados 1 Espectro Sers Del áCido Fólicounclassified
“…En estudios similares este modo de vibración es utilizado como huella digital para la determinación e identificación de E. coli [ 7,14]. Otros modos de vibración importantes presentes en el espectro SERS están relacionados con la presencia de lípidos y ácidos nucleicos presentes en la estructura de E. coli [15].…”
Section: Modos De Vibración Representativos De E Coliunclassified
“…By applying different SERS substrates, numerous groups have shown that SERS spectra of different bacterial species show different spectral features, which allows the qualitative differentiation of the species by their SERS spectra [113,117,120,124,126,[128][129][130][131][132][133][134][135][136][137][138][139][140]. The range of the investigated bacteria comprises Gram-positive as well as Gram-negative bacteria.…”
Section: Analysis Of Bulk Bacteria Samples With Sersmentioning
confidence: 99%
“…They could even discriminate three strains of E. coli from each other by simple PCA classification [130]. Some groups have investigated mixed bacterial samples and were able to tell them apart from pure cultures by PCA [130,143] or Euclidian distance [128,129]. Surprisingly, the mixed samples did not appear in the area between the pure samples but were shifted toward one constituent of the mixture [129,143] or even showed larger difference from both original components [128,130].…”
Section: Analysis Of Bulk Bacteria Samples With Sersmentioning
confidence: 99%
“…However, the several issues inherent to the nature of the technique, mainly reproducibility, still persist and lower the applicability to its wide spread use in biological applications. The detection and identification of several biological molecules such as proteins [106][107][108][109][110], DNA [111][112][113][114], and RNA [115,116] and molecular organizations such as bacteria [117][118][119][120][121][122][123][124][125][126], yeast [127][128][129], and viruses [130,131] using SERS were reported. The detection scheme could be based on either using the intrinsic fingerprint information of the molecules or molecular structures or the use of an external label.…”
Section: Detection Identification and Characterization Of Biomacrommentioning
confidence: 99%